Persepsi Petugas Customer Relation Officer Dalam Service Recovery Rekomendasi Hak Guna Bangunan di Atas Hak Pengelolaan Lahan - Putri, Ayu Adriana; Fitriati, Rachma (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
The purpose of this study is to describe what factors increase CRO's adaptability in service recovery  on  HGB  over  HPL  in  the  Capital  Investment  Office  and  the  One  Stop Integrated  Ministry  of  DKI  Jakarta  Province.  The  method  used  in  this  research  is quantitative  descriptive.  Sources  of data  were  taken  from  CRO  officers  who  were  directly involved in HGB services over HPL as many as 50 respondents. The technique of collecting data  is  done  by  distributing  and  filling  out  questionnaires.  The  results  found  that  cultural  competence, self-management, social capacity affect recovery Performance and information justice factors do not influence the Performance of CRO recovery services on HGB search services over HPL.